Magnetic resonance angiography determined variations in the circle of Willis: Analysis of a large series from a single center - Reddy Ravikanth; Babu Philip (Tzu Chi Medical Journal, 2019)
Objective: The purpose of this study is to evaluate and describe the prevalence and patterns of arterial variants in the circle of Willis (CW) seen in noncontrast three-dimensional time-of-flight magnetic resonance angiography in a series of patients with cerebral vascular accidents (CVAs). Materials and Methods: A descriptive study was undertaken in 200 patients who presented for screening for CVA in the Department of Radiodiagnosis and Imaging, St. John's Medical College Hospital, Bengaluru, from September 2014 to September 2016. Results: The most common types of CW in a single subject were anterior variant Type A and posterior variant Type E. Type A in the anterior circulation is the normal adult pattern. There is a single anterior communicating artery. The internal carotid artery bifurcates into the precommunicating segment of the anterior cerebral artery and middle cerebral artery. Type E in the posterior circulation is hypoplasia or absence of both posterior communicating arteries and isolation of the anterior and posterior parts of the circle at this level. Overall, CW variants were slightly more common in women than in men. Conclusion: Our findings show that the configuration of the CW may vary greatly in the general population. The wide range in the morphology of CW warrants further research on various races and larger populations to confirm the influence of genetic, regional, environmental, and hemodynamic factors or their combination.